Studi Numerik Unjuk Kerja Penggunaan Winglet Pada Heat Exchanger Tipe Compact - Chandra Siregar; Irfansyah Irfansyah (Rekayasa Material, Manufaktur dan Energi, 2018)
The compact heat exchanger is one type of heat exchanger which has an area of heat transfer per unit volume the largest (≥ 400 m2 / m3 for liquids and ≥ 700 m2 / m3 for gases) which is composed of fin and tube. But often found a decrease in heat transfer performance on a heat exchanger. To increase the heat transfer performance, changes are made on the surface of the fin or by adding a vortex generator. In this numerical study vortex generator was added to the winglet delta curve type which aims to determine the flow characteristics and the transfer of heat produced. This numerical study uses solidworks flow simulation software as a numerical simulation tool. Speed variations on the inlet side are 0.5 m / s, 1.15 m / s and 1.8 m / s. Simulation results were obtained by comparing fin using winglet delta curve with those without the winglet delta curve and compared to adding holes on the winglet delta curve. From the simulation results obtained compact heat exchanger which uses the winglet delta curve without and with holes the increase in heat transfer rate ranges from 16.43% - 30.67% compared to a heat exchanger without     a winglet delta curve.